Students’ Responses Leveling in Solving Mathematical Problem Based on SOLO Taxonomy Viewed from Multiple Intelligences - Amalia Silwana; Subanji; Muhamatsakree Manyunu; Arifah Adlina Rashahan (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2021)
This research aimed to determine the level of student response with logical-mathematical, verbal-linguistic, and visual-spatial intelligence tendency in solving mathematical problems of linear programming material based on SOLO taxonomy. The level of students’ responses as the output in this research is expected to be used as a reference by mathematics teachers to determine the appropriate learning methods and strategies in accordance with the tendency of students' multiple intelligence types. It can be useful in realizing the effectiveness of mathematics learning about what needs to improved and emphasized in learning so that all students can achieve optimal responses in solving mathematical problem and can develop their multiple intelligences. This research is descriptive qualitative research with six students in the 11thGrade of SMAN 1 Gondanglegi as research subjects: two students with logical-mathematical intelligence tendency, two students with verbal-linguistic intelligence tendency, and two students with visual-spatial intelligence tendency. Data collection was done by providing multiple intelligence classification tests, linear programming problem tests, and interviews. The result of the research showed the students’ response level in solving the mathematical problem of linear programming material based on SOLO taxonomy is that students with logical-mathematical intelligence tendency reached extended abstract response level, students with verbal-linguistic intelligence tendency reached multistructural response level, and students with visual-spatial intelligence tendency reached multistructural and relational response level.